Synthesis of Hydroxyapatite (HAp) from Green Mussel Shell As Bone Graft Material: A Review (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
Natural bone grafts that are widely used today such as autograft, allograft, and xenograft, have limitations in availability, compatibility, and risk of disease transfer. The use of synthetic bone grafts was developed as an alternative, one of which is hydroxyapatite. Hydroxyapatite (HAp) is the most commonly used calcium phosphate bioceramic in biomedical applications as it has a chemical composition similar to human bone and teeth. Hydroxyapatite can be synthesized using chemical precursors containing calcium such as Ca(NO3)2 and phosphate such as (NH4)2HPO4 and Na2HPO4. In addition to using chemicals, HAp can also be synthesized from natural sources, such as mussel shells, eggshells, fish bones, and coral that are rich in calcium content. Methods that can be used in HAp synthesis include dry, wet, thermal, or a combination of these methods. Each different synthesis method can produce different morphology, size, and crystallinity phase. This study summarizes several HAp synthesis methods, which include wet, high temperature, and sonochemical methods, aiming to determine the best method in the synthesis of hydroxyapatite (HAp) as bone graft material from green mussel shell waste. The analysis showed that HAp synthesized by microwave irradiation method is the most suitable for use as synthetic bone graft material. This method produces HAp with high crystallinity and has a Ca/P ratio of 1.68 which is closest to the stoichiometric ratio of HAp which is 1.67.